A smart-card-enabled privacy preserving E-prescription system. - Yanjiang Yang (IEEE Transactions on information technology in biomedicine)
Within the overall context of protection of health care information, privacy of prescription data needs special treatment. First, the involvement of diverse parties, especially nonmedical parties in the process of drug prescription complicates the protection of prescription data. Second, both patients and doctors have privacy stakes in prescription, and their privacy should be equally protected. Third, the following facts determine that prescription should not be processed in a truly anonymous manner: certain involved parties conduct useful research on the basis of aggregation of prescription data that are linkable with respect to either the patients or the doctors; prescription data has to be identifiable in some extreme circumstances, e.g., under the court order for inspection and assign liability. In this paper, we propose an e-prescription system to address issues pertaining to the privacy protection in the process of drug prescription. In our system, patients' smart cards play an important role. For one thing, the smart cards are implemented to be portable repositories carrying up-to-date personal medical records and insurance information, providing doctors instant data access crucial to the process of diagnosis and prescription. For the other, with the secret signing key being stored inside, the smart card enables the patient to sign electronically the prescription pad, declaring his acceptance of the prescription. To make the system more realistic, we identify the needs for a patient to delegate his signing capability to other people so as to protect the privacy of information housed on his card. A strong proxy signature scheme achieving technologically mutual agreements on the delegation is proposed to implement the delegation functionality.